Design and Implementation of Image Capture for Cluster Housing Security System Based on IoT - Muhamad Arief Aryadi; Mia Galina (Department of Electrical Engineering, 2022)
The performance of IoT platforms to security systems has been implemented by some researchers in various scopes such as door, garage, and house gates. Implementing an IoT platform to the gate residential cluster is performed for entering and exiting the gate. Having an interactive system, sending an image of the visitor to the resident, and operating an automatic gate are three main features developed in this work. Using Arduino board to MATLAB and Arduino to Blynk interconnections is implemented to perform those three features. This work describes the entire process of its creation from hardware requirements, through the system's design, up to the simulation test from the running process. From the simulation test, the device can interact with the incoming visitor within 1.33 seconds on average, with the accuracy of the played voice being 100% correct, and the image sent to the 100% proper corresponding resident is done within the time taken to respond to permission granted is 1.56 seconds, while the permission denied takes 1.39 seconds.